Inside out and outside in: psychodynamic clinical theory and psychopathology in contemporary multicultural contexts - Joan Berzoff (ed.); Laura Melano Flanagan (ed.); Patricia Hertz (ed.) (Lanham : Rowman & Littlefield Publishers, 2011)
"Over the past decade, Inside Out and Outside In has become a very important book among mental health practitioners in a variety of disciplines that deal with individuals in their complex social environments. Revised and updated throughout, the thirdedition builds on this foundation and adds a new chapter on cognitive behavioral theory and practice and a new chapter on relational and intersubjective theories to more fully meet the needs of both students and practitioners today. The third edition ofInside Out and Outside In maintains the book's respectful tone and empathetic voice while making many new additions. The chapter on affective disorders now includes bipolar disorders. Two other chapters update content on psychodynamic theory and race and gender. This edition also offers new research on schizophrenia and personality disorders. Other key updates include linking trauma theory with attachment, as well as attending to client systems, including couples, throughout the book. This new edition further deepens our understanding of the biopsychosocial contexts in which clinical theory and practice occur, particularly in multicultural settings. It offers ways to clearly understand theories and clinical disorders in their biological and socialcontexts and provides key updates on new developments in the biopsychosocial domain"--Provided by publisher.
Keywords: Psychodynamic Psychotherapy; Psychoanalytic Interpretation; Psychology Pathological; Psychoanalytic Therapy; Psychoanalytic Theory; Personality Development; Medicine; Applied Sciences